Legal Support of Industrial Accident Prevention - STRELNYK, Viktoria; CHURILOVA, Tetiana; HRES, Natalia; MYRONENKO, Tetiana (Journal of Advanced Research in Law and Economics, 2019)
The research analyzes the need to recognize and enshrine in legislation the general principles of prevention from and control over industrial hazardous events. The finding of the most effective integrated interstate approach to the solution of environmental safety and compliance matters remains an urgent challenge. The global environmental disaster may be avoided only if all members of the global community implement unified approaches and standards, regardless of the level of their economic development. The preservation of the latter takes on particular significance on a global scale and depends on the level and quality of development and implementation of political, economic and organizational mechanisms of the European environmental integration in the country. In general, the authors’ team deepens and develops the methodology of the functional approach to the study of legal phenomena. Practical application of the research results is possible provided to the availability of a mechanism for action coordination, incident response, prompt information exchange in the event of an emergency and state responsibility. In the study, the authors substantiated the need to develop uniform requirements to the industrial facility inspection system aimed at reducing harm, improving the use of natural resources with the greatest environmental protection at minimum cost is justified.